Effect of resveratrol administration on ovarian morphology, determined by transvaginal ultrasound for the women with polycystic ovary syndrome (PCOS). Issue 2 (28th July 2022) - Hashemi Taheri, Amir Pejman; Moradi, Behnaz; Radmard, Amir Reza; Sanginabadi, Milad; Qorbani, Mostafa; Mohajeri-Tehrani, Mohammad Reza; Shirzad, Nooshin; Hosseini, Saeed; Hekmatdoost, Azita; Asadi, Sedigheh; Samadi, Majid; Mansour, Asieh
Abstract: Intake of resveratrol has been associated with improved ovarian morphology under in vitro and in the animal models; however, this finding has not been confirmed in trials. The aim of our study was, therefore, to use a placebo-controlled approach with the detailed assessment of the ovarian morphology by applying transvaginal ultrasound to examine the effectiveness of this therapeutic approach in this group of women. The mean age of all participants was 28·61 (sd 4·99) years, with the mean BMI of 28·26 (sd 5·62) kg/m 2 . Resveratrol therapy, as compared with placebo, was associated with a significantly higher rate of improvement in the ovarian morphology ( P = 0·02). Women who received resveratrol had a more dominant follicle than those getting placebo, with a significant reduction in the ovarian volume ( P < 0·05). However, the number of follicle count per ovary (FNPO), stromal area (SA), ovarian echogenicity and distribution of follicles were not significantly altered ( P > 0·05). Forty-one women with polycystic ovary syndrome (PCOS) were randomly assigned (1:1) to 3 months of daily 1000 mg resveratrol or placebo. Random assignment was done by blocked randomisation. Our primary endpoints were the change in the ovarian volume, SA and antral FNPO from the baseline to 3 months. Secondary endpoints were improvement in the distribution of follicles and ovarian echogenicity. Differences between the resveratrol and control groups were evaluated by Chi-square, Fisher's exact test and repeated-measures ANOVA. Treatment with resveratrol significantly reduced the ovarian volume and polycystic ovarian morphology, thus suggesting a disease-modifying effect in PCOS.